NEED ANALYSIS FOR PODCAST DEVELOPMENT IN TEACHING SPEAKING DURING PANDEMIC COVID 19 - Helfany Amsa; Nofriza Efendi (Pendekar: Jurnal Pendidikan Berkarakter, 2022)
Abstrak: Penelitian ini berfokus pada pengembangan podcast dalam pengajaran speaking yang dilakukan melalui analisa kebutuhan. Penelitian ini merupakan tahap awal dari Research development model ADDIE yaitu tahapan analisa kebutuhan. Tahapan analisa kebutuhan dilakukan dengan metode survey yang dilakukan dengan wawancara dan penyebaran kuesioner. Wawancara dan kuesioner digunakan sebagai teknik pengambilan data. Wawancara dilakukan untuk menggali lebih dalam informasi yang berkaitan dengan kesulitan mahasiswa dalam melakukan interaksi dalam kelas speaking dan analisa kebutuhan untuk pengembangan podcast. Kuesioner digunakan untuk mendapatkan data kuantitaif mengenai kebutuhan siswa untuk pengembangan podcast. Studi ini melaporkan hasil kebutuhan mahasiswa dan dosen pengampu mata kuliah speaking terhadap pengembangan podcast yang akan dilakukan serta kesulitan yang ditemukan dalam pengajaran speaking selama masa pandemic covid 19.Abstract:  This research focuses on developing podcasts in teaching speaking which is done through needs analysis. This research is the initial stage of the ADDIE model research development, namely the needs analysis stage. Stages of needs analysis is done by survey method which is done by interview and distributing questionnaires. Interviews and questionnaires were used as data collection techniques. Interviews were conducted to dig deeper into information related to students' difficulties in interacting in speaking classes and to analyze needs for podcast development. Questionnaires were used to obtain quantitative data regarding students' needs for podcast development. This study reports the results of the needs of students and lecturers who support speaking courses on the podcast development that will be carried out as well as the difficulties found in teaching speaking during the COVID-19 pandemic.